Impact of Epigenetic Regulation on the Pathogenesis and Inheritance of Rheumatoid Arthritis - Vora, Ahana; Zhang, Cindy Xin Wen (Journal of Biology and Life Science, 2024)
Rheumatoid Arthritis (RA) is an autoimmune disease that causes joint and bone damage through inflammation. This chronic condition is often linked to genetic and environmental factors. With advancements in the field of epigenetics, increased speculation has arisen to understand the impact of DNA methylation, microRNAs, and histone modifications on the progression of RA. Studies have indicated that dysregulation in epigenetics significantly contributes to the pro-inflammatory landscape of RA. Furthermore, separate lines of evidence have shown that altered epigenetic patterns due to the disease can be inherited. This literature review aims to compile all available evidence regarding how epigenetic mechanisms contribute to the pathogenesis and inheritance of RA.